Analisis Keausan dan Umur Pakai Screw pada Mesin Injection Molding untuk Material Polyamide (PA9T) Menggunakan Pendekatan Archard Wear Law - Yulia Widhianti; Ahmad Syarif (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2026)
In manufacturing industries utilizing the injection molding process, the reliability of production machinery is a critical factor influencing production performance, product quality, and operational efficiency. Machine component failures, particularly in the screw, can lead to downtime, reduced productivity, and increased maintenance and production costs. Therefore, an analysis of component wear and service life is essential to support the implementation of effective maintenance strategies. This study aims to analyze the wear rate and service life of screws used in injection molding machines at PT XYZ. The investigation focuses on the effect of processing polyamide (PA9T) plastic material and compares the performance of coated and uncoated screws in terms of component durability. The research methodology includes direct observation of a Fanuc Roboshot α-S150 injection molding machine, wear analysis, and service life estimation using the Archard Wear Law approach. The results indicate that the coated screw has an actual service life of approximately 650,000 shots, whereas the uncoated screw has a service life of approximately 600,000 shots. Thus, the use of a coated screw increases component service life by 8.33% compared to an uncoated screw. These findings suggest that surface coating enhances screw resistance to wear mechanisms occurring during the processing of polyamide (PA9T) material. Furthermore, the study demonstrates that wear analysis can contribute to improved productivity through the implementation of regular and effective machine maintenance practices.